Clinical Characteristics of Children with Refrative Amblyopia at Cipto Mangunkusumo National Referral Hospital - Yulia, Dian Estu; Barliana, Julie Dewi; Sitorus, Rita Sita; Putri, Meuthia Rana; Soeharto, Diajeng Ayesha (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
Amblyopia, commonly referred to as 'lazy eye’, manifests as a reduction in best corrected visual acuity (BCVA) in the absence of detectable ocular structural abnormalities. Refractive amblyopia specifically denotes a subtype of amblyopia arising from uncorrected refractive errors. A retrospective descriptive analysis was conducted on medical records of all pediatric patients with refractive amblyopia at the Department of Ophthalmology, Cipto Mangunkusumo Kirana National Referral Hospital, Jakarta, Indonesia in 2018 to 2022. A total of 391 eyes of 224 patients were included. Median age was 8 (5-18) years, with majority being older than 7 years of age (58.7%). Leading method of treatment was with spectacles alone (80.4%). Overall amblyopia improvement was mostly observed after six months of treatment. In conclusion, refractive amblyopia at our hospital was highly prevalent among children. Thus, early detection and treatment of refractive errors in children is essential to prevent refractive amblyopia.